Високоефективні напівпровідникові перетворювачі електроенергії на основі високочастотних магнітних підсилювачів - Яськів, Володимир Іванович (Національний технічний університет "Харківський політехнічний інститут", 2021)
Дисертація на здобуття наукового ступеня доктора технічних наук за спеціальністю 05.09.12 "Напівпровідникові перетворювачі електроенергії" - Тернопільський національний технічний університет імені Івана Пулюя, Тернопіль, 2021. Дисертація присвячена вирішенню науково-прикладної проблеми вдосконалення методів та засобів перетворення параметрів електроенергії в напівпровідникових перетворювачах на основі високочастотних магнітних підсилювачів. Запропоновано методи для вирішення актуальної задачі створення загальної концепції побудови високоефективних компактних високочастотних НПЕ в широкому діапазоні вихідних потужностей (десятки Вт – одиниці кВт) та забезпечення високого рівня їх уніфікації задля мінімізації матеріальних, фінансових та інтелектуальних затрат на етапі як розробки перетворювачів, так і їх виробництва. Розроблено інтервальну макромодель енергетичної характеристики високочастотного магнітного підсилювача у вигляді функції від вихідних параметрів перетворювачів електроенергії, яку покладено в основу методу оптимізації масо-габаритних та цінових характеристик осердь магнітних підсилювачів в широкому діапазоні вихідних потужностей з метою створення технології проектування уніфікованого ряду НПЕ з оптимальними масо-габаритними характеристиками осердь ВМП. З метою побудови НПЕ з високим рівнем струму навантаження запропоновано та досліджено методи організації паралельної роботи як імпульсних стабілізаторів постійної напруги на високочастотних магнітних підсилювачах, так і високочастотних нерегульованих транзисторних інверторів, які забезпечують рівномірний розподіл струму навантаження між окремими стабілізаторами та високу стабільність синхронної та синфазної комутації високочастотних інверторів. Запропоновано новий метод побудови керованих перетворювачів на основі ВМП з виходом на змінному струмі із широким діапазоном регулювання частоти вихідної напруги, який забезпечує низький рівень електромагнітних завад та високий рівень динамічних характеристик. Запропоновано та досліджено методи побудови ІСПН на ВМП з синхронним випрямленням, в яких керування польовими транзисторами випрямляча здійснюється безпосередньо у функції напруг високочастотного силового трансформатора інвертора, а керування польовим транзистором у вихідному фільтрі у функції уже наявних в НПЕ напруг дроселів насичення ВМП без введення будь-яких додаткових елементів чи схем керування ними. Результати проведених експериментальних досліджень електромагнітної сумісності НПЕ на ВМП засвідчили низький рівень їх електромагнітних завад випромінювання. Задля покращення електромагнітної сумісності запропоновано та досліджено використання в цих перетворювачах коректорів коефіцієнта потужності, що реалізовують принцип ОСС (One Cycle Control). Проведено дослідження в частотній області НПЕ на ВМП при замкнутому зворотному зв’язку з використанням пакета прикладних програм PSPICE. Результати роботи використано при проектуванні керованого трьохканального імпульсного джерело живлення електричних гальм системи електроприводу антени великого діаметра (ДНТП "ТЕХАС-К", м. Тернопіль), імпульсного джерела живлення автомобільного радіосканера (ТОВ НВФ "Інтеграл", м. Тернопіль), джерела живлення радіопередавальних та приймальних пристроїв систем дистанційного керування енергооб’єктами та обліку електроенергії (ТОВ ТКБР "Стріла", м. Тернопіль).

Dissertation on achieving the scientific degree Doctor of Technical Science in specialty 05.09.12 Semiconductor Power Converters – Ternopil Ivan Puluj National Technical University, Ternopil, 2021. The dissertation is devoted to a solution of an actual scientific and applied problem of improvement of methods and means of electric power conversion parameters in semiconductor converters on the basis of high-frequency magnetic amplifiers. Methods for solving the topical problem of creating a general concept for high-efficiency compact high-frequency power converters design with a wide range of output powers (tens of W - kW), and ensuring a high level of their unification to minimize material, financial and intellectual costs at the stages of power converters development and production were proposed. There was developed an interval macromodel of energy characteristic of high-frequency magnetic amplifier as a function of power converters’ output parameters. It is the basis of the method for optimizing mass and dimensions, and price of MagAmp cores in a wide range of output power to create the design technology for unified series of power converters with optimal MagAmp core weight and dimensions characteristics. In order to design power converters with a high level of load current, the methods of parallel operation organization for both pulse DC voltage regulators on high-frequency magnetic amplifiers, and high-frequency unregulated transistor inverters are proposed and investigated. Uniformity of the load current distribution between the individual stabilizers is ensured by a single feedback on the output voltage and does not depend on the technological variance of the MagAmp cores’ parameters. The high stability of synchronous and in-phase switching of high-frequency inverters is determined by the only independent level of the remagnetisation rate limit of MagAmp core with rectangular hysteresis loop in the inverters positive feedback loops by output voltages. Both methods are implemented without the introduction of any additional feedback loops, provided that there are no specialized control circuits and additional power supply for them, at minimal use of discrete elements for the entire system. The result is achieved by coherence and interaction of electromagnetic processes in semiconductor and magnetic elements. A new method for design of controlled power converters based on high-frequency MagAmps with AC output with a wide range of output voltage frequency regulation is proposed. It provides a low level of electromagnetic interference and a high level of dynamic characteristics. A method for design of power converters based on high-frequency MagAmps with synchronous rectification is proposed and investigated. It allows control of field-effect transistors of the rectifier directly as a function of the voltages of the inverter’s high-frequency power transformer, and excludes the flow of short circuit currents in the rectifier without introducing any additional elements or control circuits for them. To achieve a higher efficiency of the power converters, it is proposed to control the MOSFET, which is used instead of the diode in the output filter of the power converter, in the function of the already existing MagAmp voltages. Moreover, this method of output filter realization does not require any additional elements or control circuits. The carried out experimental study of the proposed methods confirms their effectiveness and ensuring high efficiency of the power converters in a 100% range of load current variation. The results of experimental studies of the electromagnetic compatibility of power converters based on high-frequency MagAmps showed a low level of their electromagnetic interference. To improve the electromagnetic compatibility, the use of power factor correctors based on the principle of OCC (One Cycle Control), has been proposed and investigated. A mathematical model of Magamp power converter was derived. It was investigated in a frequency domain for a closed feedback loop using PSPICE software package. The results were used in the design of a controlled three-channel switching power supply for electric brakes of the electric drive system of large diameter antenna (State Scientific Production Firm TEXAS-K, Ternopil,) switching power supply of car radio scanner (Scientific Production Firm Integral, Ternopil,) power supply radio transmitting and receiving devices of systems for remote control of power objects and the accounting of electric power (Ternopil Design Office Strila, Ternopil.)
High-efficiency semiconductor power converters based on high-frequency magnetic amplifiers
Keywords: автореферат дисертації; високочастотний магнітний підсилювач; прямокутна петля гістерезису; паралельна робота; синхронний випрямляч; інтервальна модель енергетичної характеристики; high-frequency magnetic amplifier; rectangular hysteresis loop; parallel operation; synchronous rectifier; interval model of energy characteristic; 621.314